Split and partially entwined sciatic nerve following closed reduction of a dislocated hip prosthesis. Issue 6 (21st June 2020) - Wong, Jenn Shiunn; Ng, Chong Yew; Suresh, Priya; Keenan, Jonathan
Abstract : We present a case of split and partially entwined sciatic nerve by a femoral prosthesis following closed reduction of a dislocated hip replacement. This complication is very rare and there are only few cases reported in the literature, with even less accompanied by supporting MRI. We present MRI features of a split and partially entwined sciatic nerve around a hip prosthesis.